Riparian Forest Quality Index Modification: Inclusion of the Social Component in the Assessment of the Riparian Quality of the Burío-Quebrada Seca River Micro-Watershed - Araya-Yannarella, Fabián (2017)
This research was based on the comparison of the results obtained by applying the Riparian Quality Index-QBR (Munné et al., 2003) and the Riparian Quality Index modified-QBRm (Araya y Fernández, 2011) in six areas of the Burío-Quebrada Seca river micro-watershed, located in the provinces of Alajuela and Heredia, Costa Rica. The objective was to analyze the status of riparian vegetation by modifying the original index (QBR) with the inclusion of the social component (QBRm). The results of the application of the QBR index was 95 points ("very good" quality) at sampling points 1 and 2 (upper area of micro-watershed), 40 and 45 points ("bad" quality) at sampling points 3 and 4, respectively (middle area of micro-watershed), and 15 and 10 points ("very poor" quality) at the sampling points 5 and 6, respectively (lower area of micro-watershed). The results obtained from the application of QBRm index maintained the same trend and no statistically significant differences (CI 95% p: 0, 092) appeared. The QBRm index can be used to complement the strictly biological component of the QBR index and to contribute with decisions related to the integral management of the micro-watershed.